A p-GaN HEMT Voltage Reference With High Line Sensitivity and Power Supply Rejection Ratio - Pingyu Cao; Kepeng Zhao; Yihao Xu; Harm Van Zalinge; Sang Lam; Ping Zhang; Miao Cui; Fei Xue (IEEE Journal of the Electron Devices Society, 2025)
A monolithically integrated voltage reference based on p-GaN HEMT technology is demonstrated in this work. The proposed two-stage structure can improve the stability of the generated reference voltage over a wide range of the supply voltage and temperature. The static and dynamic performance was measured at various temperatures. Experimental results indicate that the output voltage is stable at 1.3 V when the supply voltage rises from 2.8 V to 40 V, with a line sensitivity of 0.035%/V at room temperature. When the measurement temperature increases to $250~{^{° }}$ C, the generated reference voltage slightly decreases to 1.25 V with a temperature coefficient of −22.1 ppm/°C. The power supply rejection ratio of this work is competitive, as the power supply rejection ratio changes from −46.64 dB to −56.2 dB, in which the noise frequency varies from 10 Hz to 5 MHz. The voltage variation of the generated reference voltage is relatively small when the frequency exceeds 5 MHz. The results show that the proposed work is particularly suitable for all-GaN monolithic integration circuits that require thermally stable bias voltages with high immunity to the supply voltage variation.